Policies, Programmes and Enrolment of Tea Tribe Children at Primary Level: Status Survey - Begum, Sultana; Islam, Quazi Ferdoushi (THE PRIMARY TEACHER, 2022)
Education is a major indicator of social and economic development of any country and its people. There is a history of education rights all over the world. In the Universal/United Nations Declaration on Human Rights Article 26 (1) emphasises that “Everyone has the right to education. Education shall be free, at least in the elementary and fundamental stages. Elementary education shall be compulsory.” Article 21A of Indian constitution also highlight that “The state shall endeavour to provide free and compulsory education to all children in the age group of six to fourteen years as a fundamental right.” (Hence, given the RTE act which is also called for inclusive and education of disadvantaged groups.) Moreover, the tea garden worker’s children come under this group. The tea garden workers of Assam are commonly known as ‘Tea Tribe’. The tea tribe community constitutes 20 per cent of the total population of Assam. Government has put up massive plans, provisions and acts that also has clauses dealing with the education of tea garden children. In spite of this backdrop and provisioning, the educational status of tea garden children at primary level is abysmally low. This paper highlights the enrolment rate of education of tea garden children of Assam with special reference to Lakhimpur district. The analysis of the data is based on primary sources. This paper also draws conclusions pertaining to the low enrolment in spite of government initiative at the State and center level